Pengaruh Board Size, Firm Size, Firm Age Dan Sales Growth Terhadap Kinerja Keuangan Perusahaan Perbankan Syariah Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2013-2022 - Puspita, Indah Lia; Ramadhani, Yoga Adit (Universitas Malahayati, 2024)
This study aims to examine the effect of Board Size, Firm Size, Firm Age and Sales Growth on the financial performance of Islamic Banking companies listed on the Indonesia Stock Exchange (IDX) in the period 2013-2022. This type of research uses quantitative methods with secondary data. The population in this study were Islamic banking companies listed on the Indonesia Stock Exchange (IDX) in the 2013-2022 period. The sampling method used is saturated sampling, meaning that all members of the population are used as samples. A total of 4 companies for 10 years and a total sample of 40 annual financial report data. Hypothesis testing in this study was tested using multiple linear regression analysis using SPSS version 26. The results of this study indicate that Board Size, Firm Age and Sales Growth have a significant effect on company financial performance, while Firm Age has no significant effect on company financial performance.